1996
DOI: 10.1302/0301-620x.78b5.0780777
|View full text |Cite
|
Sign up to set email alerts
|

Medial Epicondylectomy or Ulnar-Nerve Transposition for Ulnar Neuropathy at the Elbow?

Abstract: W e carried out a prospective randomised study comparing medial epicondylectomy with anterior transposition for the treatment of ulnar neuropathy at the elbow. The mean follow-up period was 4.5 years and we assessed the patients neurologically and orthopaedically.Neither procedure appeared to have a significant effect on elbow function. Our study showed better results after medial epicondylectomy; in particular patient satisfaction was higher than after ulnar nerve transposition. There were no significant diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(44 citation statements)
references
References 11 publications
0
38
0
4
Order By: Relevance
“…6,7,13,17) Deciding on the most effective procedure can be difficult, given the excellent results claimed. 1,2,14,18) Despite the high frequency of UNE, there is no clear consensus on the indications for surgery or the most appropriate surgical technique. [14][15][16]19,20,[23][24][25]30,41) Operative management includes simple decompression (or``decompression in situ''); medial epicondylectomy, either alone or in combination with simple decompression; and anterior transposition.…”
Section: Introductionmentioning
confidence: 99%
“…6,7,13,17) Deciding on the most effective procedure can be difficult, given the excellent results claimed. 1,2,14,18) Despite the high frequency of UNE, there is no clear consensus on the indications for surgery or the most appropriate surgical technique. [14][15][16]19,20,[23][24][25]30,41) Operative management includes simple decompression (or``decompression in situ''); medial epicondylectomy, either alone or in combination with simple decompression; and anterior transposition.…”
Section: Introductionmentioning
confidence: 99%
“…For partial epicondylectomy, improvement percentages have been reported as 67% good to excellent results in 27 patients [21], 75% good to excellent results in 60 patients [30], 75% good to excellent results in 55 patients [37], 79% good to excellent results in 80 patients [8], and 80% good to excellent results in 45 patients [28]. Several studies have shown that after total epicondylectomy, patients experienced an overall subjective improvement of approximately 90% [9,14,16,25,40]. In studies of anterior transposition of ulnar nerve in patients with severe-stage cubital tunnel syndrome, the improvement percentages were reported as 72% to 100% [12,13,15,23].…”
Section: Discussionmentioning
confidence: 99%
“…Much of the controversy of the operative procedure for carpal tunnel syndrome is the method by which to release the ligament but most surgeons would agree that successful management of patients with carpal tunnel syndrome depends on complete release of the flexor retinaculum [1,3,6,17,22]. In contrast for cubital tunnel syndrome, there are numerous operative procedures that have been described for the treatment of cubital tunnel syndrome ranging from simple decompression, medial epicondylectomy to transposition of the ulnar nerve [2,4,7,9,12,13,14,15,16,19,21,23,24,25,26,27,29,30,31]. These procedures vary not only in surgical technique but also in the correction of the etiologic factors.…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous operative procedures described for the treatment of cubital tunnel syndrome ranging from simple decompression, medial epicondylectomy to transposition of the ulnar nerve [2,4,7,9,12,13,14,15,16,19,21,23,24,25,26,27,29,30,31]. With each operative procedure, there have been reports of excellent patient outcome as well as postoperative complications [10,11,18,28].…”
Section: Introductionmentioning
confidence: 99%